Peruvian Masculinities: A review - Villa-Palomino, Julio (2023)
This article is an overview of Peruvian studies and research on men and masculinities. This field of study has around forty years of existence and Peru has contributed with scholarship that advances the field both theoretically and methodologically. This overview identifies seven main areas prioritized by Peruvian social scientists: 1) the construction of masculinities; 2) masculinities and gender violence; 3) reconstruction and relearning of masculinities; 4) paternities; 5) emotions and corporality; 6) representations of masculinities in the media and literature; and 7) masculinities and gender diversity. I conclude this overview by highlighting new ways for research.